Government advertising ... - New South Wales. Audit Office; New South Wales. Audit Office (Sydney, NSW : Audit Office of NSW.)
Executive summary: "In NSW, the Government Advertising Act 2011 (the Act) requires government advertising campaigns with a likely expenditure of over 50,000 dollars to be independently peer reviewed before they can be launched. Seventy-four campaigns were peer reviewed in 2015-16. There is a hierarchy of legislation and guidance documents relating to government advertising. These include the Act, the NSW Government Advertising Guidelines (Advertising Guidelines) and the NSW Government Advertising Handbook (Advertising Handbook). (Refer to Section 1.2 for further information). The Advertising Guidelines require peer reviews to assess campaigns against three specific criteria... The Strategic Communications and Events branch of the Department of Premier and Cabinet (the Department) manages the peer review process, including coordinating and allocating peer reviewers. Government agencies submit proposed advertising campaigns to the Department to facilitate review. Public sector staff employed in marketing or communication roles can apply to become a peer reviewer. This audit assessed the effectiveness of peer review in providing assurance that government advertising is needed and cost effective.."
Description based on: 2015/2016
Keywords: Government advertising -- Australia -- New South Wales -- Auditing -- Periodicals; Government advertising -- New South Wales -- Auditing -- Periodicals; Government publicity -- Australia -- New South Wales -- Auditing -- Periodicals; Government publicity -- New South Wales -- Auditing -- Periodicals; Transparency in government -- Australia -- New South Wales -- Auditing -- Periodicals; Transparency in government -- New South Wales -- Auditing -- Periodicals; Government publicity -- Auditing; New South Wales; Electronic journals; Periodicals